2011
DOI: 10.3390/molecules161210556
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Artesunate on the Expression of EGFR and ABCG2 in A549 Human Lung Cancer Cells and a Xenograft Model

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer death worldwide. Clinical and laboratory studies have suggested that multi-targeting approaches against neoplastic cells could help to increase patient survival and might reduce the emergence of cells that are resistant to single-target inhibitors. Artesunate (ART) is one of the most potent and rapidly acting antimalarial agents known, and it also exerts a profound cytotoxic activity toward cancer cells and reverses multi-drug resistance. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Langroudi et al [119] Implanted mouse spontaneous mammary ductal carcinoma, started when tumors reached 500 mm 3 Ma et al [199] A549 human non-small cell lung carcinoma mouse xenograft; started when tumors reached 100 mm 3 , artesunate (60 or 120 mg/kg/day, p.o., 2 weeks).…”
Section: Lai Andmentioning
confidence: 99%
“…Langroudi et al [119] Implanted mouse spontaneous mammary ductal carcinoma, started when tumors reached 500 mm 3 Ma et al [199] A549 human non-small cell lung carcinoma mouse xenograft; started when tumors reached 100 mm 3 , artesunate (60 or 120 mg/kg/day, p.o., 2 weeks).…”
Section: Lai Andmentioning
confidence: 99%
“…Studies have identified that artemisinin has inhibitory effect on A549 human lung adenocarcinoma cells, and that its mechanism of action may be to inhibit cell proliferation, induce apoptosis and cell cycle arrest (54,55). Thus, the co-administration of artemisinin derivatives with other anti-cancer agents may increase the concentration of those anti-cancer drugs in the cell (56). In the present study, it was identified that artesunate can inhibit the proliferation, apoptosis and invasion of EOMA cells in vitro by reducing the expression of HIF-1α, VEGF-A and VEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is increasing evidence that ART has anti-cancer capability [16]; ART has been shown to have a profound cytotoxic action against several tumors, such as Kaposi’s sarcoma, hepatocellular carcinoma, non-small cell lung cancer and cervical cancer [17,18,19,20]. However, whether ART can inhibit the growth of bladder cancer has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%